let n be Nat; :: thesis: for f being PartFunc of REAL,REAL

for Z being Subset of REAL st Z c= dom f & f is_differentiable_on n,Z holds

for a, b being Real st a < b & [.a,b.] c= Z & ((diff (f,Z)) . n) | [.a,b.] is continuous & f is_differentiable_on n + 1,].a,b.[ holds

ex g being PartFunc of REAL,REAL st

( dom g = Z & ( for x being Real st x in Z holds

g . x = (f . a) - ((Partial_Sums (Taylor (f,Z,x,a))) . n) ) & g . a = 0 & g | [.a,b.] is continuous & g is_differentiable_on ].a,b.[ & ( for x being Real st x in ].a,b.[ holds

diff (g,x) = - (((((diff (f,].a,b.[)) . (n + 1)) . x) * ((a - x) |^ n)) / (n !)) ) )

let f be PartFunc of REAL,REAL; :: thesis: for Z being Subset of REAL st Z c= dom f & f is_differentiable_on n,Z holds

for a, b being Real st a < b & [.a,b.] c= Z & ((diff (f,Z)) . n) | [.a,b.] is continuous & f is_differentiable_on n + 1,].a,b.[ holds

ex g being PartFunc of REAL,REAL st

( dom g = Z & ( for x being Real st x in Z holds

g . x = (f . a) - ((Partial_Sums (Taylor (f,Z,x,a))) . n) ) & g . a = 0 & g | [.a,b.] is continuous & g is_differentiable_on ].a,b.[ & ( for x being Real st x in ].a,b.[ holds

diff (g,x) = - (((((diff (f,].a,b.[)) . (n + 1)) . x) * ((a - x) |^ n)) / (n !)) ) )

let Z be Subset of REAL; :: thesis: ( Z c= dom f & f is_differentiable_on n,Z implies for a, b being Real st a < b & [.a,b.] c= Z & ((diff (f,Z)) . n) | [.a,b.] is continuous & f is_differentiable_on n + 1,].a,b.[ holds

ex g being PartFunc of REAL,REAL st

( dom g = Z & ( for x being Real st x in Z holds

g . x = (f . a) - ((Partial_Sums (Taylor (f,Z,x,a))) . n) ) & g . a = 0 & g | [.a,b.] is continuous & g is_differentiable_on ].a,b.[ & ( for x being Real st x in ].a,b.[ holds

diff (g,x) = - (((((diff (f,].a,b.[)) . (n + 1)) . x) * ((a - x) |^ n)) / (n !)) ) ) )

assume A1: ( Z c= dom f & f is_differentiable_on n,Z ) ; :: thesis: for a, b being Real st a < b & [.a,b.] c= Z & ((diff (f,Z)) . n) | [.a,b.] is continuous & f is_differentiable_on n + 1,].a,b.[ holds

ex g being PartFunc of REAL,REAL st

( dom g = Z & ( for x being Real st x in Z holds

g . x = (f . a) - ((Partial_Sums (Taylor (f,Z,x,a))) . n) ) & g . a = 0 & g | [.a,b.] is continuous & g is_differentiable_on ].a,b.[ & ( for x being Real st x in ].a,b.[ holds

diff (g,x) = - (((((diff (f,].a,b.[)) . (n + 1)) . x) * ((a - x) |^ n)) / (n !)) ) )

let a, b be Real; :: thesis: ( a < b & [.a,b.] c= Z & ((diff (f,Z)) . n) | [.a,b.] is continuous & f is_differentiable_on n + 1,].a,b.[ implies ex g being PartFunc of REAL,REAL st

( dom g = Z & ( for x being Real st x in Z holds

g . x = (f . a) - ((Partial_Sums (Taylor (f,Z,x,a))) . n) ) & g . a = 0 & g | [.a,b.] is continuous & g is_differentiable_on ].a,b.[ & ( for x being Real st x in ].a,b.[ holds

diff (g,x) = - (((((diff (f,].a,b.[)) . (n + 1)) . x) * ((a - x) |^ n)) / (n !)) ) ) )

assume A2: ( a < b & [.a,b.] c= Z & ((diff (f,Z)) . n) | [.a,b.] is continuous & f is_differentiable_on n + 1,].a,b.[ ) ; :: thesis: ex g being PartFunc of REAL,REAL st

( dom g = Z & ( for x being Real st x in Z holds

g . x = (f . a) - ((Partial_Sums (Taylor (f,Z,x,a))) . n) ) & g . a = 0 & g | [.a,b.] is continuous & g is_differentiable_on ].a,b.[ & ( for x being Real st x in ].a,b.[ holds

diff (g,x) = - (((((diff (f,].a,b.[)) . (n + 1)) . x) * ((a - x) |^ n)) / (n !)) ) )

consider g being PartFunc of REAL,REAL such that

A3: ( dom g = Z & ( for x being Real st x in Z holds

g . x = (f . a) - ((Partial_Sums (Taylor (f,Z,x,a))) . n) ) ) by Lm7;

take g ; :: thesis: ( dom g = Z & ( for x being Real st x in Z holds

g . x = (f . a) - ((Partial_Sums (Taylor (f,Z,x,a))) . n) ) & g . a = 0 & g | [.a,b.] is continuous & g is_differentiable_on ].a,b.[ & ( for x being Real st x in ].a,b.[ holds

diff (g,x) = - (((((diff (f,].a,b.[)) . (n + 1)) . x) * ((a - x) |^ n)) / (n !)) ) )

thus ( dom g = Z & ( for x being Real st x in Z holds

g . x = (f . a) - ((Partial_Sums (Taylor (f,Z,x,a))) . n) ) & g . a = 0 & g | [.a,b.] is continuous & g is_differentiable_on ].a,b.[ & ( for x being Real st x in ].a,b.[ holds

diff (g,x) = - (((((diff (f,].a,b.[)) . (n + 1)) . x) * ((a - x) |^ n)) / (n !)) ) ) by A1, A2, A3, Lm10; :: thesis: verum

for Z being Subset of REAL st Z c= dom f & f is_differentiable_on n,Z holds

for a, b being Real st a < b & [.a,b.] c= Z & ((diff (f,Z)) . n) | [.a,b.] is continuous & f is_differentiable_on n + 1,].a,b.[ holds

ex g being PartFunc of REAL,REAL st

( dom g = Z & ( for x being Real st x in Z holds

g . x = (f . a) - ((Partial_Sums (Taylor (f,Z,x,a))) . n) ) & g . a = 0 & g | [.a,b.] is continuous & g is_differentiable_on ].a,b.[ & ( for x being Real st x in ].a,b.[ holds

diff (g,x) = - (((((diff (f,].a,b.[)) . (n + 1)) . x) * ((a - x) |^ n)) / (n !)) ) )

let f be PartFunc of REAL,REAL; :: thesis: for Z being Subset of REAL st Z c= dom f & f is_differentiable_on n,Z holds

for a, b being Real st a < b & [.a,b.] c= Z & ((diff (f,Z)) . n) | [.a,b.] is continuous & f is_differentiable_on n + 1,].a,b.[ holds

ex g being PartFunc of REAL,REAL st

( dom g = Z & ( for x being Real st x in Z holds

g . x = (f . a) - ((Partial_Sums (Taylor (f,Z,x,a))) . n) ) & g . a = 0 & g | [.a,b.] is continuous & g is_differentiable_on ].a,b.[ & ( for x being Real st x in ].a,b.[ holds

diff (g,x) = - (((((diff (f,].a,b.[)) . (n + 1)) . x) * ((a - x) |^ n)) / (n !)) ) )

let Z be Subset of REAL; :: thesis: ( Z c= dom f & f is_differentiable_on n,Z implies for a, b being Real st a < b & [.a,b.] c= Z & ((diff (f,Z)) . n) | [.a,b.] is continuous & f is_differentiable_on n + 1,].a,b.[ holds

ex g being PartFunc of REAL,REAL st

( dom g = Z & ( for x being Real st x in Z holds

g . x = (f . a) - ((Partial_Sums (Taylor (f,Z,x,a))) . n) ) & g . a = 0 & g | [.a,b.] is continuous & g is_differentiable_on ].a,b.[ & ( for x being Real st x in ].a,b.[ holds

diff (g,x) = - (((((diff (f,].a,b.[)) . (n + 1)) . x) * ((a - x) |^ n)) / (n !)) ) ) )

assume A1: ( Z c= dom f & f is_differentiable_on n,Z ) ; :: thesis: for a, b being Real st a < b & [.a,b.] c= Z & ((diff (f,Z)) . n) | [.a,b.] is continuous & f is_differentiable_on n + 1,].a,b.[ holds

ex g being PartFunc of REAL,REAL st

( dom g = Z & ( for x being Real st x in Z holds

g . x = (f . a) - ((Partial_Sums (Taylor (f,Z,x,a))) . n) ) & g . a = 0 & g | [.a,b.] is continuous & g is_differentiable_on ].a,b.[ & ( for x being Real st x in ].a,b.[ holds

diff (g,x) = - (((((diff (f,].a,b.[)) . (n + 1)) . x) * ((a - x) |^ n)) / (n !)) ) )

let a, b be Real; :: thesis: ( a < b & [.a,b.] c= Z & ((diff (f,Z)) . n) | [.a,b.] is continuous & f is_differentiable_on n + 1,].a,b.[ implies ex g being PartFunc of REAL,REAL st

( dom g = Z & ( for x being Real st x in Z holds

g . x = (f . a) - ((Partial_Sums (Taylor (f,Z,x,a))) . n) ) & g . a = 0 & g | [.a,b.] is continuous & g is_differentiable_on ].a,b.[ & ( for x being Real st x in ].a,b.[ holds

diff (g,x) = - (((((diff (f,].a,b.[)) . (n + 1)) . x) * ((a - x) |^ n)) / (n !)) ) ) )

assume A2: ( a < b & [.a,b.] c= Z & ((diff (f,Z)) . n) | [.a,b.] is continuous & f is_differentiable_on n + 1,].a,b.[ ) ; :: thesis: ex g being PartFunc of REAL,REAL st

( dom g = Z & ( for x being Real st x in Z holds

g . x = (f . a) - ((Partial_Sums (Taylor (f,Z,x,a))) . n) ) & g . a = 0 & g | [.a,b.] is continuous & g is_differentiable_on ].a,b.[ & ( for x being Real st x in ].a,b.[ holds

diff (g,x) = - (((((diff (f,].a,b.[)) . (n + 1)) . x) * ((a - x) |^ n)) / (n !)) ) )

consider g being PartFunc of REAL,REAL such that

A3: ( dom g = Z & ( for x being Real st x in Z holds

g . x = (f . a) - ((Partial_Sums (Taylor (f,Z,x,a))) . n) ) ) by Lm7;

take g ; :: thesis: ( dom g = Z & ( for x being Real st x in Z holds

g . x = (f . a) - ((Partial_Sums (Taylor (f,Z,x,a))) . n) ) & g . a = 0 & g | [.a,b.] is continuous & g is_differentiable_on ].a,b.[ & ( for x being Real st x in ].a,b.[ holds

diff (g,x) = - (((((diff (f,].a,b.[)) . (n + 1)) . x) * ((a - x) |^ n)) / (n !)) ) )

thus ( dom g = Z & ( for x being Real st x in Z holds

g . x = (f . a) - ((Partial_Sums (Taylor (f,Z,x,a))) . n) ) & g . a = 0 & g | [.a,b.] is continuous & g is_differentiable_on ].a,b.[ & ( for x being Real st x in ].a,b.[ holds

diff (g,x) = - (((((diff (f,].a,b.[)) . (n + 1)) . x) * ((a - x) |^ n)) / (n !)) ) ) by A1, A2, A3, Lm10; :: thesis: verum